Representações sociais sobre a educação formal para alunos do ensino médio no município de Pato Branco Paraná - Pizzolatto, Marcos André (2020)
The present investigation privileged the study of Social Representations on formal education for students of 1st year of high school in a public school located in the municipality of PatoBranco, state of Paraná. Initially, the work examined the History of education in Brazil, including the reform of Law 13,415 of 2017, after which it referred to the theoretical approach of Social Representations, as well as the relevance of this theory aimed at education. Next, the methodological procedures used in the investigation were treated. The data were collected through the application of free evocation questionnaires designed specifically for this study, part of which consisted of identification questions, a question of free evocation through the inductive term School, another question that allowed the importance of evocations and essay questions in the hierarchies. which subjects should justify the evocations induced by the term inducer. For the analysis and discussion of the questions of free evocation, the theory of the central nucleus and the qualitative analysis were used. The results of the analysis of public school students indicated that the researched students socially represent the School as a space for study and learning capable of generating future opportunities and, simultaneously, perceived as the place of reproduction of the necessary and craved social relations, however, it is , also represented as a social imposition compressed in a space of formalities and boredom that, being seen in this way, carries meanings that represent an unwanted school. Finally, in our considerations, we will promote the effort to propose the breaking of these contradictions through a more multi-dimensional education: technical, political and subjective. Where the role of interpersonal and the role of the teacher in this democratic and affective process as education should be highlighted.